Characterisation of PVL-Positive Staphylococcus argenteus from the United Arab Emirates - Stefan Monecke; Sindy Burgold-Voigt; Sascha D. Braun; Celia Diezel; Elisabeth M. Liebler-Tenorio; Elke Müller; Rania Nassar; Martin Reinicke; Annett Reissig; Abiola Senok; Ralf Ehricht (MDPI AG, 2024)
Staphylococcus argenteus is a recently described staphylococcal species that is related to Staphylococcus aureus but lacks the staphyloxanthin operon. It is able to acquire both resistance markers such as the SCCmec elements and mobile genetic elements carrying virulence-associated genes from S. aureus. This includes those encoding the Panton-Valentine leukocidin (PVL), which is associated mainly with severe and/or recurrent staphylococcal skin and soft tissue infections. Here, we describe the genome sequences of two PVL-positive, mecA-negative S. argenteus sequence type (ST) 2250 isolates from the United Arab Emirates in detail. The isolates were found in a dental clinic in the United Arab Emirates (UAE). Both were sequenced using Oxford Nanopore Technology (ONT). This demonstrated the presence of temperate bacteriophages in the staphylococcal genomes, including a PVL prophage. It was essentially identical to the published sequence of phiSa2wa_st78 (GenBank NC_055048), a PVL phage from an Australian S. aureus clonal complex (CC) 88 isolate. Besides the PVL prophage, one isolate carried another prophage and the second isolate carried two additional prophages, whereby the region between these two prophages was inverted. This "flipped" region comprised about 1,083,000 bp, or more than a third of the strain's genome, and it included the PVL prophage. Prophages were induced by Mitomycin C treatment and subjected to transmission electron microscopy (TEM). This yielded, in accordance to the sequencing results, one or, respectively, two distinct populations of icosahedral phages. It also showed prolate phages which presumptively might be identified as the PVL phage. This observation highlights the significance bacteriophages have as agents of horizontal gene transfer as well as the need for monitoring emerging staphylococcal strains, especially in cosmopolitan settings such as the UAE.